Impact of the COVID-19 pandemic on outcomes of acute ischemic stroke patients treated with endovascular therapy: A multicenter Canadian study - Shenghua Zhu; Ammar Alam; Rebecca Thornhill; Vered Tsehmaister-Abitbul; Grant Stotts; Hailey Pettem; Richard Aviv; Ronit Agid; Aleksandra Pikula; Jai Jai Shiva Shankar; Genevieve Milot; Brian Van Adel; et al. (PLoS ONE, 2025)
Objective The novel coronavirus disease 2019 (COVID-19) pandemic led to the implementation of wide-ranging institutional infection control protocols. The purpose of this study is to determine the effect of the pandemic on outcomes of large vessel occlusion (LVO) acute ischemic stroke (AIS) patients treated with endovascular therapy (EVT). Materials and methods Data were obtained from prospectively collected quality improvement stroke databases at six Canadian comprehensive stroke centres from March 11, 2020 to March 11, 2021. This patient cohort was compared to pre-pandemic patients consecutively treated with EVT from March 11, 2019 to March 10, 2020. The primary outcome is a 90-day modified Rankin Score (mRS). The secondary outcomes are angiographic time metrics. Results A total of 1329 EVT patients (pre-pandemic n = 666) were included. The initial NIHSS was statistically significantly lower in the pandemic cohort. Other baseline patient characteristics were comparable between the two periods. Median (interquartile range, IQR) time from last seen normal (LSN) to emergency department (ED) (172 (68–316) vs 210 (97–382) min; p = 0.0001), LSN to puncture (235 (160–378) vs 280 (184–475); p < 0.0001), computed tomography (CT) to angiographic table (68 (44–108) vs 84 (57–125) min; p = 0.002), ED to angiographic table (65 (37–96) vs 80 (50–112) min; p = 0.001), CT to recanalization (117 (84–156) vs 130 (89–173) min; p = 0.038) and LSN to recanalization (279 (198–453) vs 327 (219–561) min; p = 0.002) were longer in the pandemic period as compared to the pre-pandemic. There were no significant differences in median time from angiographic table to arterial puncture (13 (8–19) vs 12 (9–16) min; p = 0.70) or arterial puncture to first pass (21 (14–31) vs 20 (14–30) min; p = 0.50). Patients were more likely to have favourable outcomes (mRS at 90 days score of ≤ 2) post-EVT pre-pandemic than pandemic (53% vs 44%; p = 0.02). Furthermore, analysis of the time interval from “LSN to arterial puncture” in relation to functional outcomes showed that the percentage of unfavorable outcomes increased among patients who underwent EVT within 240 minutes. Specifically, the rate of unfavorable outcomes rose from 32.9% to 42.9% (p = 0.37 for intervals under 150 minutes) and from 41.6% to 52.3% (p = 0.15 for intervals between 151 and 240 minutes) when comparing pre-pandemic to pandemic periods. However, the detrimental effect associated with the pandemic was diminished in patients who received EVT beyond 240 mins (p = 1.0). Conclusion In this multicenter study involving six Canadian stroke centers, patients exhibited a higher probability of unfavorable long-term functional outcomes following EVT during the pandemic period compared to those in the pre-pandemic cohort, particularly during the first year of the pandemic.